Personal qualities of juvenile offenders’ deformation features - Karipbaev, Zh.; Complak, K. (Bulletin of the Karaganda University “Law Series”, 2019)
The article focuses on the peculiarities of the violation of the personal qualities of juvenile offenders and on the issue of approval. This article deals with the problem that requires a detailed study of the personality traits of offenders and criminals to understand the genesis of offenses and the misconduct of minors. Currently in our opinion, «juvenile’s administrative offense» implies the violation of public law, the security, health, life, rights and freedoms of citizens, property and governance, social danger, unlawful, the intended action of juvenile delinquencies and administrative liability in current legislation. In accordance with this case, we can depict the personality traits of deviating behavioral juvenile delinquents. In its turn, the analysis of individual peculiarities of juvenile offenders suggests that all juvenile offenders, who deliberately violate public order and commit administrative offenses, are directly involved in deformation of personal qualities of juveniles. In the article, using the various research methods, the current legislation bases the definition of effective ways of legal regulation by describing the legal definition and peculiarities of the administrative action. At present, special attention is paid to the personality traits of juvenile offenders. This is due to the need for research, as the increase in juvenile delinquency among adolescents is an important factor in drawing attention to this issue.